Factors Affecting Purchase Decision of Life Insurance Policy of Customer in Chitwan - Bista, Manish Bahadur; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Life insurance policy enjoys a unique position in the field of investments and should be judged in this light. The policy owner behaviour towards life insurance than the conventional savings and protection view. The objective of this research was to assess the intentions of people towards purchasing decision of life insurance, to analyze the awareness level of life insurance in Chitwan and to examine the relationship among perception, attitudes, awareness and purchase decision.Methods: An analytical cross-sectional study was conducted among 150 policy holder respondents in Bharatpur, Chitwan, Nepal. Non probability purposive sampling technique was used for data collection. Data was analyzed by using descriptive and inferential statistical tools. In this research Independent Variables was (Purpose of Buying, perception and evaluation alternatives, trust) while dependent Variable was (Purchase of Life Insurance Policy). Data was analysed by using SPSS 20. P-value